Anti-CD20 Depletes Meningeal B Cells but Does Not Halt the Formation of Meningeal Ectopic Lymphoid Tissue. Issue 4 (July 2021) - Brand, Rosa Margareta; Friedrich, Verena; Diddens, Jolien; Pfaller, Monika; Romana de Franchis, Francesca; Radbruch, Helena; Hemmer, Bernhard; Steiger, Katja; Lehmann-Horn, Klaus
Abstract : Objective: To investigate whether anti-CD20 B-cell-depleting monoclonal antibodies (ɑCD20 mAbs) inhibit the formation or retention of meningeal ectopic lymphoid tissue (mELT) in a murine model of multiple sclerosis (MS). Methods: We used a spontaneous chronic experimental autoimmune encephalomyelitis (EAE) model of mice with mutant T-cell and B-cell receptors specific for myelin oligodendrocyte glycoprotein (MOG), which develop meningeal inflammatory infiltrates resembling those described in MS. ɑCD20 mAbs were administered in either a preventive or a treatment regimen. The extent and cellular composition of mELT was assessed by histology and immunohistochemistry. Results: ɑCD20 mAb, applied in a paradigm to either prevent or treat EAE, did not alter the disease course in either condition. However, ɑCD20 mAb depleted virtually all B cells from the meningeal compartment but failed to prevent the formation of mELT altogether. Because of the absence of B cells, mELT was less densely populated with immune cells and the cellular composition was changed, with increased neutrophil granulocytes. Conclusions: These results demonstrate that, in CNS autoimmune disease, meningeal inflammatory infiltrates may form and persist in the absence of B cells. Together with the finding that ɑCD20 mAb does not ameliorate spontaneous chronic EAE with mELT, our data suggest that mELT may have yet unknown capacities that are independent of B cells and contribute to CNS autoimmunity.